The circRNA–microRNA code: emerging implications for cancer diagnosis and treatment. Issue 4 (18th February 2019) - Verduci, Lorena; Strano, Sabrina; Yarden, Yosef; Blandino, Giovanni
Abstract : Circular RNAs (circRNAs) comprise an emerging new class of endogenous RNAs expressed abundantly by the eukaryotic transcriptome. They are characterized by a covalently closed loop structure, resulting in RNA molecules that are more stable than linear RNAs. A growing number of studies indicate that circRNAs play critical roles in human diseases and show great potential as biomarkers and therapeutic targets. The molecular events determined by circRNA activity, the circRNA code, involve other types of noncoding RNA molecules, primarily microRNAs, long noncoding RNAs, and RNA‐binding proteins. Herein, we mainly focus on the circRNA–microRNA code, showing how this relationship impacts the regulation of gene expression in cancer. The emerging roles for circRNAs in oncogenic pathways highlight new perspectives for the detailed molecular dissection of cancer pathogenesis and, at the same time, offer new opportunities to design innovative therapeutic strategies. Here, we review recent research advancements in understanding the biogenesis, molecular functions, and significance of circRNAs in cancer diagnosis and treatment. Abstract : Circular RNAs (circRNAs) are promising cancer biomarkers that have been detected in different body fluids like saliva, plasma, and blood. They work in association with other molecules, such as RNA‐binding proteins. Particularly interesting are the relations between microRNAs and circRNAs. The emerging circRNA–microRNA code plays an important role in regulating gene expression in cancer.